2018
DOI: 10.1097/md.0000000000011771
|View full text |Cite
|
Sign up to set email alerts
|

Serum C-peptide concentration and prostate cancer

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The advancement of PCa may be associated with markers of insulin resistance, such as increased glucose and glycohemoglobin levels. Research has indicated that males with increased levels of glucose, insulin, and glycated hemoglobin are more vulnerable to PCa-related death or metastases [31][32][33][34][35]. Studies have shown that individuals with higher plasma glucose, insulin, and glycated hemoglobin levels have a higher risk of developing metastatic disease or dying from PCa [36][37][38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…The advancement of PCa may be associated with markers of insulin resistance, such as increased glucose and glycohemoglobin levels. Research has indicated that males with increased levels of glucose, insulin, and glycated hemoglobin are more vulnerable to PCa-related death or metastases [31][32][33][34][35]. Studies have shown that individuals with higher plasma glucose, insulin, and glycated hemoglobin levels have a higher risk of developing metastatic disease or dying from PCa [36][37][38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…No difference in the serum C-peptide level was observed between the nBMI patients and the healthy controls. The meta-analysis by Guo et al [ 76 ] indicated that the C-peptide concentration was not associated with an increased risk of prostate cancer. On the other hand, the studies of Arcidiacono et al [ 77 ] indicated that the level of C-peptide may correlate with the development of Barrett’s esophageal carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…level, have shown lower risks in relation to PCa, [2][3][4][5] especially localised PCa. However, these findings could be due to delayed detection of PCa in men with obesity and type 2 diabetes mellitus (T2DM), both common conditions in men with insulin resistance and also related to lower levels of prostate-specific antigen (PSA) and potentially less PCa screening.…”
mentioning
confidence: 95%
“…Insulin resistance is related to a higher risk of several forms of cancer 1 but in relation to prostate cancer (PCa), the commonest cancer in men in high‐income countries, evidence remains unclear. Some markers of insulin resistance, including elevated plasma glucose and glycated haemoglobin (HbA1c), a marker of long‐term blood glucose level, have shown lower risks in relation to PCa, 2–5 especially localised PCa. However, these findings could be due to delayed detection of PCa in men with obesity and type 2 diabetes mellitus (T2DM), both common conditions in men with insulin resistance and also related to lower levels of prostate‐specific antigen (PSA) and potentially less PCa screening 6–8 .…”
Section: Introductionmentioning
confidence: 99%